PRE-SEQUENCES AND SPEECH ACTS IN CEBUANO RADIO HEALTH COMMERCIALS IN CEBU CITY - Ceska Marie R Apalla; Keeshia Joy S San Juan; Rowanne Marie R Maxilom (Universitas Muhammadiyah Surakarta, 2017)
This research attempted to identify and analyze the Cebuano-Bisaya radio health commercials using Schegloff’s (2007) framework on pre-sequences with the support of Yule’s (1996) speech act theory. Thirty (30) Cebuano-Bisaya radio health commercials were gathered from two selected radio stations. The results revealed that representatives were the most dominant function in speech acts that reflected in pre-sequences specifically with pre-offers and pre-announcements through drama and testimonial categories which are often used in medicinal product commercials. In advertising strategies, Cebuano-Bisaya commercials use Representatives and Expressive as persuasive devices in addressing the advertisers’ intended message to the target audience. Also, Cebuano-Bisaya commercials used Representatives and Expressive as an appeal to suggest an intention for the listener to buy advertised products.Keywords: Cebuano, commercial, health, pre-sequences, radio, speech acts